MORPHOREGRESSION AND FIRST SIZE AT MATURITY OF GOLDSTRIPE SARDINELLA (SARDINELLA GIBBOSA) FROM BALI STRAIT WATERS - Prawira A. R. P. Tampubolon; Nyoman Dati Pertami; Arief Wujdi (Indonesian Fisheries Research Journal, 2021)
Bali Strait was one of the highest density areas for small pelagic fish in Indonesian Fisheries Management Area (FMA)-573 with goldstripe sardinella (Sardinella gibbosa) as was one of the abundant species in the catch. The aims of this study were to reveal the morphoregression characteristics and the first size of maturity for Sardinella gibbosa in Bali Strait waters. A total of 1.282 goldstripe sardinella were measured in total length (TL), fork length (FL), and standard length (SL)) and weighed during the study. All of the length measurement methods were highly related to the weight, which were W = 4 x 10-6 TL3,1686 (R² = 0,9817); W = 4 x 10-6 FL3,2334 (R² = 0,9732); and W = 1 x 10-5 SL3,0239 (R² = 0,9656), respectively. Among all the measurement methods, total length estimated the weight more accurately than the others. The growth pattern of goldstripe sardinella in this study were various based on the measurement method, sex, and the maturity level of the fish. A total of 800 individuals were dissected and their gonads examined. The sex was identified by visual characteristics. The size at 50% maturity for goldstripe sardinella in Bali Strait was 148 mm TL for male and 155 mm TL for female. Most of the caught fish were under the size at 50% maturity.